Adolescent substance use screening in primary care: validity of computer self-administered vs. clinician-administered screening - Harris, Sion Kim (Subst Abus, 2015)
BACKGROUND: Computer self-administration may help busy pediatricians’ offices increase adolescent substance use screening rates efficiently and effectively, if proven to yield valid responses. The CRAFFT screening protocol for adolescents has demonstrated validity as an interview, but a computer self-entry approach needs validity testing. The aim of this study was to evaluate the criterion validity and time efficiency of a computerized adolescent substance use screening protocol implemented by self-administration or clinician-administration. METHODS: 12- to 17-year-old patients coming for routine care at three primary care clinics completed the computerized screen by both self-administration and clinician-administration during their visit. To account for order effects, we randomly assigned participants to self-administer the screen either before or after seeing their clinician. Both were conducted using a tablet computer and included identical items (any past-12-month use of tobacco, alcohol, drugs; past-3-months frequency of each; and six CRAFFT items). The criterion measure for substance use was the Timeline Follow-Back, and for alcohol/drug use disorder, the Adolescent Diagnostic Interview, both conducted by confidential research assistant-interview after the visit. Tobacco dependence risk was assessed with the self-administered Hooked on Nicotine Checklist (HONC). Analyses accounted for the multi-site cluster sampling design. RESULTS: Among 136 participants, mean age was 15.0±1.5 yrs, 54% were girls, 53% were Black or Hispanic, and 67% had ≥3 prior visits with their clinician. Twenty-seven percent reported any substance use (including tobacco) in the past 12 months, 7% met criteria for an alcohol or cannabis use disorder, and 4% were HONC-positive. Sensitivity/specificity of the screener were high for detecting past-12-month use or disorder and did not differ between computer and clinician. Mean completion time was 49 seconds (95%CI 44-54) for computer and 74 seconds (95%CI 68-87) for clinician (paired comparison p<0.001). CONCLUSIONS: Substance use screening by computer self-entry is a valid and time-efficient alternative to clinician-administered screening.